Functionally distinct ERAP1 and ERAP2 are a hallmark of HLA-A29-(Birdshot) Uveitis. (12th September 2018) - Kuiper, Jonas J W; Setten, Jessica van; Devall, Matthew; Cretu-Stancu, Mircea; Hiddingh, Sanne; Ophoff, Roel A; Missotten, Tom O A R; Velthoven, Mirjam van; Den Hollander, Anneke I; Hoyng, Carel B; James, Edward; Reeves, Emma; et al.
Abstract: Birdshot Uveitis (Birdshot) is a rare eye condition that affects HLA-A29-positive individuals and could be considered a prototypic member of the recently proposed 'MHC-I (major histocompatibility complex class I)-opathy' family. Genetic studies have pinpointed the endoplasmic reticulum aminopeptidase ( ERAP1 ) and ( ERAP2 ) genes as shared associations across MHC-I-opathies, which suggests ERAP dysfunction may be a root cause for MHC-I-opathies. We mapped the ERAP1 and ERAP2 haplotypes in 84 Dutch cases and 890 controls. We identified association at variant rs10044354, which mediated a marked increase in ERAP2 expression. We also identified and cloned an independently associated ERAP1 haplotype (tagged by rs2287987) present in more than half of the cases; this ERAP1 haplotype is also the primary risk and protective haplotype for other MHC-I-opathies. We show that the risk ERAP1 haplotype conferred significantly altered expression of ERAP1 isoforms in transcriptomic data (n = 360), resulting in lowered protein expression and distinct enzymatic activity. Both the association for rs10044354 (meta-analysis: odds ratio (OR) [95% CI]=2.07[1.58–2.71], P  = 1.24 × 10(−7)) and rs2287987 (OR[95% CI]: =2.01[1.51–2.67], P  = 1.41 × 10(−6)) replicated and showed consistent direction of effect in an independent Spanish cohort of 46 cases and 2103 controls. In both cohorts, the combined rs2287987-rs10044354 haplotype associated with Birdshot more strongly than either variant alone [meta-analysis: P =3.9 × 10(−9)]. Finally, we observed that ERAP2 protein expression is dependent on the ERAP1 background across three European populations (n = 3353). In conclusion, a functionally distinct combination of ERAP1 and ERAP2 are a hallmark of Birdshot and provide rationale for strategies designed to correct ERAP function for treatment of Birdshot and MHC-I-opathies more broadly.